2021
DOI: 10.1111/pops.12777
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice, Political Ideology, and Interest: Understanding Attitudes Toward Affirmative Action in Brazil

Abstract: Few public policies have been as consequential or divisive as affirmative action. Proponents have argued for the need for equity and the redress of past and present discrimination, whereas opponents enlist claims over individual liberty and merit. Scholars have examined support to affirmative action, asking to what extent citizens' support is shaped by their political ideology, interest, prejudice, or some combination thereof. Much work to date has focused on the United States, where disentangling theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In 2012, the Brazilian government initiated the quota law requesting all public universities to allocate 50% of the admission vacancies to public high school graduates based on the criteria such as race and income. Although time has not quelled controversy over this policy ( Turgeon and Habel, 2021 ), extant research suggests no significant difference in academic performance between quota and non-quota students, indicating that this policy is worthy of recognition ( Vidigal, 2018 ; Pelegrini et al, 2022 ). In the United States, both SAT and ACT examination has undergone significant changes to boost enrollment of lower socioeconomic and racial/ethnic groups ( Hurwitz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the Brazilian government initiated the quota law requesting all public universities to allocate 50% of the admission vacancies to public high school graduates based on the criteria such as race and income. Although time has not quelled controversy over this policy ( Turgeon and Habel, 2021 ), extant research suggests no significant difference in academic performance between quota and non-quota students, indicating that this policy is worthy of recognition ( Vidigal, 2018 ; Pelegrini et al, 2022 ). In the United States, both SAT and ACT examination has undergone significant changes to boost enrollment of lower socioeconomic and racial/ethnic groups ( Hurwitz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a survey conducted by Caregnato and Oliven, covering a representative sample of 900 Brazilians living in the state of Rio Grande do Sul, found that 75.8% of Brazilians supported the 2012 federal law that established racial and class quotas for all federal universities (Caregnato & Oliven, 2017, p. 179;Turgeon & Habel, 2022). Results differ, however, depending on factors like race and income, as well as the type of affirmative action under scrutiny.…”
Section: A Narrative Transition: the Expansion Of Dialogue About Race...mentioning
confidence: 99%
“… Anunciação et al, 2020 , Bobocel et al, 1998 , Fenn, 2000 , Garg et al, 2020 , Graham et al, 2020 , Instituto de Pesquisa Econômica Aplicada – Ipea, 2011 , Johnson et al, 2018 , Locomotiva, 2020 , Market research and online surveys in Brazil., 2022 , Martins-Filho et al, 2021 , Rogbeer et al, 2021 , Rothgerber et al, 2021 , Sears et al, 1997 , Sinhoretto et al, 2020 , Turgeon and Habel, 2021 , Weitzer, 1999 …”
Section: Uncited Referencesmentioning
confidence: 99%